MONOLITHIC DISK FOR THE FAST CHROMATOGRAPHIC SEPARATION - Nurul Hidayat Aprilita; Rania Bakry; Christian W Huck; Guenther K Bonn (Indonesian Journal of Chemistry, 2005)
Poly(styrene/divinylbenzene) (PS/DVB) monolithic disk was prepared by in situ free-radical copolymerization of styrene and divinylbenzene in the presence of decanol and tetrahydrofuran as porogens. PS/DVB monolithic disks were produced in two different lengths 1.5 mm and 3 mm. The disks were used in reversed phase chromatography of proteins with 0.2 % trifuoroacetic acid (TFA) and 0.2 % TFA in acetonitrile as mobile phase A and B, respectively. The effect of gradient rate, flow rate, temperature and disk length on the separation of proteins were also studied. PS/DVB monolithic disks allow the rapid separation of proteins in reversed phase chromatography.